Impossible is not so easy a life in politics - Rocamora, Joel; Bughaw (Firm) (Quezon City Bughaw, 2020)
They are the footprints of a life spent working for difficult political causes. This is not history; half of the book is on Duterte, and on federalism. Except for a few, more academic pieces, most of the selections are short, easy-to-digest analyses.
"Bughaw is an imprint of Ateneo de Manila University Press" -- Title page.
Includes bibliographical references.
In English.
Keywords: Duterte, Rodrigo Roa -- 1945-.; Federal government -- Philippines; Philippines -- Politics and government -- 1986-.